Evaluación de la cantidad de ceniza conteniendo silicio para disminuir el daño causado, por spodoptera... - Callao López, Frank Anthony (2014)
In Moyobamba city, High May Valley, in the environments of the Ecology Faculty - of Tarapoto San Martín National University, during June- August, 2014 the execution ofthe project was carried out: Evaluation of the ash quantity containing silicon to diminish the caused hurt, by Spodoptera frugiperda in Oryza sativa "Rice", in Moyobamba. The specific aims were, to determine the ash quantity added to the soil, with major in crease of protection of Oryza sativa to diminish hmts of Spodoptera frugiperda. And to describe the characteristics of Spodoptera frugiperda in his biological cycle, fed on leaves of rice proceeding from soils treated with ash of brickyard. The problem statement is it possible that the silica content in the puliton, ash incorporated into the soil, reduce the damage of Spodoptera frugiperda in Oryza sativa, in Moyobamba?. Between the variables were, the independent variable, the silicon content in the ash of brick, and as the dependent variable, damage caused by Spodoptera frugiperda. The Hypothesis to demonstrating was: If, we locate quantities of ash, containing Silicon, in the soil, the hurt caused by Spodoptera frugiperda in Oryza sativa diminishes significantly. The results obtained in all the tests of the consumption of foliage 1 larva 1 day, the ANV A has showed high significance and in Duncan test to 0.05 of probability, the control treatment (without ash, without ash brick) and the treatment one (Tl) were the most consumed or ingested by the S. frugiperda larvae, numerically the most consumed was the witness. The lower value of consumption was introduced by thc T4. In plant height, all of the evaluations carried out, ANV A indicates high significance between the treatments evaluated. Duncan test at the 0.05 leve! of probability shows that the treatments T2, (1.5 kilos of ash), Tl (1.0 kilo of ash) and TO (witness) were higher in plant height in all ages ofthe gumbo limbo unfit for consumption ofthe plague in study. In height of plant, in all the realized evaluations, the ANV A indicates high significance between the evaluated treatments. Duncan test shows to 0.05 of probability that the treatments T2, (1.5 kilos of ash), Tl (1.0 kilo of ash) and TO (witness) they were top in height of plants in all the ages of the suitable selling plants for the consumption of the plague in study. In fresh biomass expressed in (gr) /plant, AN OVA (Analysis of variance), in all the assessments were presented high significance, in all oftbe evidence. In addition, the highest value of fresh biomass and dry was introduced by the Tl treatment (1.0 kilo of ash), the lowest dose of ash between the treatments evaluate. The amount of brick ash (ash of rice husks) determined to add to the ground with greater increase in protection of Oryza sativa to lessen damages of Spodoptera frugiperda, were: The quantities of 2.5, 2.0 and 1.5 kilos of brickyard ash, incorporated in 8 kilos of land for the almacigueras. Between the characteristics of Spodoptera frugiperda in its life cycle, fed with sheets of rice from soil treated with ash brick, were observed the following: Fewer positions (eggs), only 180 per adult, other researchers found that in raisings in greenhouse, occurred more than 800 units per adult. The sizes ofthe larvae that reached were lower, only 38 mm, compared to the size oflarvae reported by other investigators ( 40, 42 up to 45 mm). Key words: Spodoptera frugiperda, Duncan test.